Validity of the Velocomp PowerPod compared with the Verve Cycling InfoCrank Power Meter - Merkes, P. F. J.; Menaspà, P.; Abbiss, C. R. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine the validity of the Velocomp PowerPod power meter in comparison with the Verve Cycling InfoCrank power meter. Methods: This research involved 2 separate studies. In study 1, 12 recreational male road cyclists completed 7 maximal cycling efforts of a known duration (2 times 5 s and 15, 30, 60, 240, and 600 s). In study 2, 4 elite male road cyclists completed 13 outdoor cycling sessions. In both studies, power output of cyclists was continuously measured using both the PowerPod and InfoCrank power meters. Maximal mean power output was calculated for durations of 1, 5, 15, 30, 60, 240, and 600 seconds plus the average power output in study 2. Results: Power output determined by the PowerPod was almost perfectly correlated with the InfoCrank (r>.996; P<.001) in both studies. Using a rolling resistance previously reported, power output was similar between power meters in study 1 (P=.989), but not in study 2 (P=.045). Rolling resistance estimated by the PowerPod was higher than what has been previously reported; this might have occurred because of errors in the subjective device setup. This overestimation of rolling resistance increased the power output readings. Conclusion: Accuracy of rolling resistance seems to be very important in determining power output using the PowerPod. When using a rolling resistance based on previous literature, the PowerPod showed high validity when compared with the InfoCrank in a controlled field test (study 1) but less so in a dynamic environment (study 2).Validität des Velocomp PowerPod im Vergleich zum Verve Cycling InfoCrank Power Meter